Sharia Pay Later Innovation in the Eyes of Generation Z: Does Brand Awareness Mediate the Effect of Sharia Religiosity and Financial Literacy on Trust? - Mawardi, Fahmi Dwi; Oktavendi, Tri Wahyu; Zakaria, Azfahanee (TIJAB (The International Journal of Applied Business), 2025)
Background: Sharia Pay Later innovation is a special attraction in the development of the Sharia Fintech world. Generation Z, with unique characteristics and becoming the majority of the population in the future, will certainly respond differently to the Sharia Pay Later Innovation. Objective: This study aims to prove the Z Generation trust model on sharia pay later innovation associated with religiosity, sharia financial literacy, and the mediation role of brand awareness. Method: This study was designed using a quantitative-explanatory approach. A Structural Equation Model (SEM) analysis was used to test the model defined in this study. Results: In the research results, when researchers provide mediating factors using brand awareness, they have not found significant results on the influence of religiosity and trust. This is caused by Generation Z's religiosity factor, which is still not strong enough to influence individual trust. When using the Islamic financial literacy factor on Generation Z Trust through Brand Awareness, it is proven to be able to influence positively and significantly. Conclusion: Generation Z's religiosity cannot build trust in Sharia Pay Later Innovations. Generation Z tends to see the Brand from the Sharia Pay Later to be able to trust their new product. In essence, individual Islamic financial literacy increases brand awareness and creates a sense of trust or not to using the Sharia Pay Later Innovation by Generation Z. Keywords: Generation Z; Trust; Innovation; Sharia Pay Later; Islamic Financial Technology